870 The Efficacy and Safety of Bariatric Surgery in Kidney Transplantation Candidates: A Systematic Review and Meta-Analysis. (19th August 2022) - Varma, J; Fernando, S; Dengu, F; Menon, V; O'Callaghan, J
Abstract: Introduction: Kidney transplantation (KT) remains a high-risk procedure which requires extensive pre-operative assessment and optimisation. Obesity is known to increase the risk of adverse post-operative consequences. Bariatric surgery (BS) is an effective solution to obesity. The authors aim to summarise the evidence for the efficacy and safety of BS in KT candidates. Method: We performed a systematic review and meta-analysis to determine the efficacy and safety of BS in patients KT candidates. A literature search of MEDLINE, EMBASE and Web of Science was conducted from inception to April 2021. The methodological quality of selected studies was assessed using the Newcastle-Ottowa tool. Our primary outcome was change in BMI, with secondary outcomes including adverse events, graft outcomes and KT rate. Results: Nine observational studies met the inclusion criteria with a total of 179 patients (48% male). Mean change in BMI following BS was -11.2 (-12.9 to -9.5, p < 0.001) within a median follow up time of 43 months (IQR 36 to 47 months). Sleeve gastrectomy (44.7%, n=80) and gastric bypass (46.9%, n=84) were the most common procedures. Median time from BS to KT was 17 months (IQR 6 to 18 months) with a mean KT rate of 80.1% (SD = 14.9). Conclusion: This review highlights that BS is both safe and efficacious for KT candidates and can be an effective means of optimising BMI prior to transplantation.